Celebrando a Paz e causando Conflitos: as diferentes facetas de Norberto de Xanten - Araujo, Vinicius Cesar Dreger de (Revista Escripturas, 2020)
Norbert of Xanten, founder of the Order of the PremonstratensianRegular Canons (1120) is an exemplary figure both in clerical reforms and in religious effervescence between the 11th and 12th centuries. We will analyze Norbert's performances as a peacemaker in Lotharingia in 1119, as an itinerant preacher and as a cause of conflicts in Magdeburg between 1126 and 1129, already as archbishop in the light of the Spielregln der Politik(by Gerd Althoff) and the Konsensuale Herrschaft(by Bernd Schneidmüller). For this purpose, we will use Vita Norberti Aas ourmain source, complemented when necessary by Vita Norberti B,the Gesta archiepiscoporum magdeburgensiumand the Annales Magdeburgenses.
Keywords: 👤 norbert of xanten